"My Child, My Choice"? Mandatory Curriculum, Sex, and the Conscience of Parents. Issue 1 (27th June 2018) - Bialystok, Lauren
ABSTRACT: In this essay Lauren Bialystok argues that the standard liberal defense of parental opt‐outs is inconsistent in the case of comprehensive sex education. Using the recent controversy over a new sex education curriculum in Ontario, Canada, as a case study, Bialystok examines the aims and effects of sex education and the self‐described conscience of opposing parents to reveal that children's interests may be harmed by deferring to parents' views on sexuality. The opt‐out strategy is a merely formal solution, which appears to be indifferent to both the strength of the justification for sex education and the content of the grounds on which parents oppose it. Being overly respectful of parental conscience in the case of sex education risks reproducing the illiberal paradigms that the curriculum is intended to erode, and thus subverts its own liberal intentions. Bialystok concludes by suggesting ways of honoring parents' right to involvement in their children's education while delivering a mandatory curriculum.